The Relationship Between Teacher Readiness in Terms of Knowledge, Literacy and Attitudes Towards Digital Transformation - Wan Hanim (Online Journal for TVET Practitioners, 2024)
As a precautionary measure to break the chain of spread of the Covid-19 epidemic, entire educational institutions around the world have been closed. This closure has had an indirect impact on students, teachers and even the institution itself. The abrupt shift in teaching and learning methods from physical classes to online classes has created a new norm for teachers and students and has had an impact on them, particularly teachers. The primary purpose of this study is to determine the level of readiness in terms of knowledge, literacy, and teacher attitudes toward digital transformation in education. The survey method was used in this study to determine the relationship between the independent variable, digital transformation in education, and the dependent variable, level of readiness in terms of knowledge, literacy, and teacher attitude. In this study, 377 rural primary school teachers from the state of Johor were asked to complete a questionnaire. Overall, the study’s findings revealed a moderately high level of readiness in terms of knowledge, literacy and teacher’s attitudes toward digital transformation in education. As an outcome of this research, teachers and educators should seize the opportunity to prepare themselves and their students in various aspects of digital transformation in order to further strengthen Malaysia’s education system. This is also support the SDG targets 4.3 and 4.4 within the context of Asia-Pacific and under the overarching theme of “Transforming Learning: Meeting the skills demand to achieve the SDGs in the Asia-Pacific”.